Investigating the Effect of the Serious Game CodeCombat on Cognitive Load in Python Programming Education - Choi, Wan Chong; Choi, Wan Chong; Choi, Iek Chong (2024 IEEE World Engineering Education Conference (EDUNINE), 2024)
Understanding the cognitive demands that programming places on young learners has become increasingly important. The Cognitive Load Theory (CLT) provided a framework with three dimensions, including intrinsic, extraneous, and germane load. Our findings derived from paired sample t-tests comparing pre-test and post-test results, indicated significant improvements in all three dimensions. Moreover, we observed notable interrelationships between these loads, where a reduction in intrinsic and extraneous loads corresponded with an increase in germane load. This suggested an effective balance between simplifying the complex subject matter and enhancing learner engagement, underlining the nuanced interplay in the learning environment facilitated by CodeCombat. These results contributed valuable insights into the role of serious games in reducing cognitive overload and enhancing learning experiences in complex subjects like programming. The study underscored the potential of interactive educational tools in early Python programming education, offering implications for primary school teaching strategies and curriculum design.